Esophageal carcinoid tumor treated by endoscopic resection. Issue 4 (16th November 2014) - Yagi, Makoto; Abe, Yasuhiko; Sasaki, Yu; Nomura, Eiki; Sato, Takeshi; Iwano, Daisuke; Yoshizawa, Kazuya; Sakuta, Kazuhiro; Kanno, Nana; Nishise, Syouichi; Ueno, Yoshiyuki
<x xml:space="preserve">Abstract</x> The present report describes a rare case of esophageal carcinoid tumor that was treated by endoscopic resection. A 43‐year‐old woman underwent esophagogastroduodenoscopy at her family clinic for screening of the upper digestive tract and a small lesion resembling a submucosal tumor was detected in the lower esophagus. A biopsy sample from the lesion was diagnosed as esophageal carcinoid tumor and the patient visited our hospital for detailed examination. The tumor was approximately 3 mm in diameter and its surface appeared to be covered with normal squamous epithelium. The tumor had a shiny reddish surface without ulceration or erosion. Magnifying endoscopy with narrow‐band imaging showed structures resembling reticular vessels under the epithelium. Endoscopic ultrasonography depicted the tumor as a low‐echoic mass within the lamina propria. Computed tomography did not detect the tumor and no metastatic lesions were evident in other organs. With the patient's informed consent, the tumor was resected using endoscopic submucosal dissection, with a sufficient free margin in both the vertical and horizontal directions. Magnifying endoscopic examination showed the resected tumor to have abundant reticular vessels. Finally, the tumor was diagnosed immunopathologically as an esophageal carcinoid tumor (neuroendocrine cell tumor, grade 1), without lymphatic or vascular invasion.